Provenance and family variation of Pinus caribaea var. hondurensis from Guatemala and Honduras, grown in Brazil, Colombia and Venezuela - Moura, Vicente Pongitory Gifoni; Dvorak, William Stephen (Pesquisa Agropecuaria Brasileira, 2001)
Pinus caribaea var. hondurensis (Sénécl) Barr. & Golf. is a tropical pine that naturally occurs in lowland areas of Belize, El Salvador, Guatemala, Honduras, Nicaragua, and eastern Mexico. It has been one of the most studied tropical pines and the one with the most commercial importance in Brazil. The objective of this work was to select the best provenances for plantations and best trees in families for the establishment of seed orchards. For that a trial with five provenances and 47 open-pollinated families was planted near Planaltina, Federal District, in the Cerrado Region of Brazil. The provenances tested were Poptun (Guatemala), Gualjoco, Los Limones, El Porvenir and Santa Cruz de Yojoa (Honduras) and assessed at 12 years of age. Poptun and Gualjoco had larger volume, and Los Limones and El Porvenir the lowest incidence of forks and foxtails. Individual tree heritabilities for volume, stem form and branch diameter were 0.34, 0.06, and 0.26 respectively. More than 90% of the trees had defects, common in unimproved P. caribaea. Selection criteria for quality traits need to be relaxed in the first generation of breeding to allow for larger genetic gains in productivity. Results from this test compared with P. caribaea var. hondurensis trials in other Brazilian, Colombian and Venezuelan sites suggest that provenance x site and family x site interactions are not as strong as in other pine species.